How does priming influence people's decision? quantitative analysis of EEG and eye movement - Yao, Peijun. (2012)
This research will find out on how the subliminal priming influence human’s decisions by using Electroencephalography (EEG) and Eye Tracker. This report will contain details on experiment design to obtain the data required for the analysis.